Improving Science Learning Outcomes Through Innovation in Cooperative Learning Models: The Effectiveness of Team Games Tournament Strategy - Devi Afriyuni Yonanda; Tia Listiani; Reza Rachmadtullah; Islahuddin; Dusu Suhandi Saputra; Yoga Ajie Pratama (Universitas Pendidikan Ganesha, 2025)
The use of inappropriate learning models in the learning process can cause students to become less active. This study aims to analyze the effect of implementing a cooperative learning model of the Teams Games Tournament (TGT) type on the learning outcomes of students in grades IVA and IVB of Elementary School. This study uses a quasi-experimental design with a quantitative approach and is included in the experimental research category. The study population consisted of all 24 students of grade IVA as the experimental group and 22 students of IVB as the control class. Data collection techniques were carried out through validity tests, reliability tests, hypothesis tests with independent sample t-tests. The results of the study showed that there was a significant increase in student learning outcomes between the experimental class and the control class. Seen from the post-test results obtained by class IVA (Experiment) with an average value of 80.29 while class IVB (Control) obtained an average value of 67.41 thus the value obtained by the experimental class has exceeded the Minimum Completion Criteria of 75. This is based on the results of the hypothesis test using the independent sample t-test obtained a sign value. (2-tailed) of 0.000 < 0.05, it can be continued that there is an influence between the experimental class using the Teams Games Tournament model which has a significant influence on the learning outcomes in grade IV of Elementary School.